2018
DOI: 10.1038/modpathol.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Optimal detection of clinically relevant mutations in colorectal carcinoma: sample pooling overcomes intra-tumoral heterogeneity

Abstract: Intra-tumoral genomic heterogeneity is a well-established biologic property of human malignancies with emerging roles in cancer progression and therapy resistance. However, its impact on the clinical utility of genomic testing in patient management remains unclear. Furthermore, best practices to account for heterogeneity in the provision of highly accurate, clinically valid molecular testing have yet to be firmly established. Genomic biomarkers for the management of colorectal carcinoma are both well-establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…In daily practice, the biopsy is still the routine way to get tumour mutant status before treatment. Considering the spatial and temporal intra-tumour molecular heterogeneity, the results for biopsy samples are yet to be consistent [11][12][13]50]. Recently, a large prospective study [50] showed that the concordance ratio between paired biopsy and resection specimens was 82% for KRAS status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In daily practice, the biopsy is still the routine way to get tumour mutant status before treatment. Considering the spatial and temporal intra-tumour molecular heterogeneity, the results for biopsy samples are yet to be consistent [11][12][13]50]. Recently, a large prospective study [50] showed that the concordance ratio between paired biopsy and resection specimens was 82% for KRAS status.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since condons 12 and 13 KRAS mutations represent the majority of RAS mutations in CRC, our results provide a reasonable representation for tumors with RAS mutation in some degree. Fourth, considering the potential discrepancy between pre-treatment biopsy and final pathology [11][12][13], only the outcome from final surgical specimen were enrolled in the study. Fifth, this was a single-center study with a limited sample size, which may be the reason why only moderate predictive value of MRI features for identifying KRAS status has been observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Some studies have indicated that sampling at three tumor-rich sites rich may reduce the negative results of DNA testing, increase the accuracy of gene detection and improve overall ITH assessment. 38 Sequencing tumor tissue DNA by multiregion sampling, however, may also be challenging. The contrast sampling method of tumor center, tumor periphery, and normal tissue obtained by diagnostic puncture method cannot achieve the function of multipoint sampling to obtain the information of intratumor heterogeneity.…”
Section: Gene Sequencing Imaging and Cell Culture Are Three "Windmentioning
confidence: 99%
“…Radiomics has frequently been adopted for subtype classification, evaluation of lymph node metastasis or distant metastasis, and prediction of treatment response or prognosis in many types of cancers [12][13][14][15]. It is regarded as somewhat difficult to assess intra-tumoral heterogeneity using a single spatially-biased biopsy [16]. Detection of unseen information reflecting intra-tumoral heterogeneity might be the main motivation for applying a radiomics approach in the oncology field.…”
Section: Introductionmentioning
confidence: 99%